Analisis Indeks Stress Deposit Rupiah dan Pengaruhnya terhadap Pinjaman Usaha Mikro, Kecil dan Menengah (UMKM) di Kabupaten/Kota Provinsi Jambi - Ardi Afrizal; Irmanelly Ermaini (Universitas Batanghari, 2021)
The purpose of this study is first to analyze the rupiah stress deposit index where the annual average for Kerinci Regency is 0.04% and Merangin Regency is 0.78%. Then for Sarolangun District by 0.16% and Batang Hari Regency by 0.34%. For Muaro Jambi Regency it was 0.31% and Tanjung Jabung Timur Regency was 0.58%. Furthermore, for Tanjung Jabung Barat Regency by 0.82% and Tebo Regency by 0.36% and Bungo Regency at 0.35% and Jambi City by 0.15% and for Sungai Penuh City by 0.13%. In general, the stress index value of the rupiah deposit on micro, small and medium business loans was the highest in three regencies, such as the districts of West Tanjung Jabung, Merangin, and Tanjung Jabung Timur. Where for the rupiah deposit stress index the highest occurred in 2017 at 0.40% and the lowest in 2016 which was 0.36%. Then the second research objective is to analyze the effect of the rupiah stress deposit index on small and medium micro loans through a panel data regression model with a constant value of 0.37, meaning that if the rupiah deposit index increases by 1%, the value of micro, small and medium business loans in regencies / cities in Jambi Province increased by 0.37% with a significance level below 5% or 0.00% negligent, meaning that partially the independent variable has an effect on the dependent variable by 47.5%.